Introduction to the Henry Stewart Talks organizational behavior series - Aldag, Ramon J. (Henry Stewart Talks, 2015)
Overview of the organizational behavior (OB) series, How the series can be used, Definitions and goals of OB, Key terms in OB, Attitudes and behaviors of interest, Individual-level attributes & processes, Organizational processes, policies & practices, Contextual characteristics, Introduction of speakers and their talks in the series